2003
DOI: 10.1210/jc.2002-021610
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Parathyroid Hormone (1–84) Whole Molecule and Parathyroid Hormone (7–84)-Like Fragments in Pseudohypoparathyroidism Type I

Abstract: PTH (7-84) has antagonistic effects on the calcemic and phosphaturic actions of PTH (1-84) whole molecule (bioPTH). Human plasma contains bioPTH and PTH (7-84)-like fragments. Using bioPTH-specific and nonspecific assays, we found that the patients with pseudohypoparathyroidism (PHP) type I with PTH-resistant hypocalcemia and hyperphosphatemia had the increased plasma levels of bioPTH and PTH (7-84)-like fragments than normal subjects (26.8 +/- 13.2 vs. 2.37 +/- 0.75 pmol/liter, P < 0.01 and 16.2 +/- 8.8 vs. 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Alfacalcidol also decreased serum PTH levels in the PHP patients in this study, and similar results were observed in previous studies [11,19,22]. Therefore, the mechanisms by which active vitamin D 3 regulates PTH secretion are functional in PHP patients.…”
Section: +supporting
confidence: 92%
See 4 more Smart Citations
“…Alfacalcidol also decreased serum PTH levels in the PHP patients in this study, and similar results were observed in previous studies [11,19,22]. Therefore, the mechanisms by which active vitamin D 3 regulates PTH secretion are functional in PHP patients.…”
Section: +supporting
confidence: 92%
“…If serum calcium is a major factor in the production of truncations, the W-PTH/T-PTH ratios in untreated PHP patients should be higher than those in normal subjects because of hypocalcemia in the PHP patients. However, a previous study also revealed significantly reduced ratios in PHP I patients [11], even though their serum calcium levels were Correlations between doses of alfacalcidol and serum PTH levels in PHP Ib patients. For all four PHP Ib patients, the alfacalcidol doses were plotted against the serum levels of W-PTH (A) and T-PTH (B), and against the W-PTH/T-PTH ratios (C).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations